Machine learning-based clinical decision support for infection risk prediction - Feng, Ting; Noren, David P.; Kulkarni, Chaitanya; Mariani, Sara; Zhao, Claire; Ghosh, Erina; Swearingen, Dennis; Frassica, Joseph; McFarlane, Daniel; Conroy, Bryan (Frontiers in Medicine, 2023)
Background: Healthcare-associated infection (HAI) remains a significant risk for hospitalized patients and a challenging burden for the healthcare system. This study presents a clinical decision support tool that can be used in clinical workflows to proactively engage secondary assessments of pre-symptomatic and at-risk infection patients, thereby enabling earlier diagnosis and treatment.Methods: This study applies machine learning, specifically ensemble-based boosted decision trees, on large retrospective hospital datasets to develop an infection risk score that predicts infection before obvious symptoms present. We extracted a stratified machine learning dataset of 36,782 healthcare-associated infection patients. The model leveraged vital signs, laboratory measurements and demographics to predict HAI before clinical suspicion, defined as the order of a microbiology test or administration of antibiotics.Our best performing infection risk model achieves a cross-validated AUC of 0.88 at 1hour before clinical suspicion and maintains an AUC>0.85 for 48-hours before suspicion by aggregating information across demographics and a set of 163 vital signs and laboratory measurements. A second model trained on a reduced feature space comprising demographics and the 36 most frequently measured vital signs and laboratory measurements can still achieve an AUC of 0.86 at 1-hour before clinical suspicion. These results compare favorably against using temperature alone and clinical rules such as the quick Sequential Organ Failure Assessment (qSOFA) score. Along with the performance results, we also provide an analysis of model interpretability via feature importance rankings.The predictive model aggregates information from multiple physiological parameters such as vital signs and laboratory measurements to provide a continuous risk score of infection that can be deployed in hospitals to provide advance warning of patient deterioration.